Modern physics : Concepts and applications - Puri, Sanjiv (Delhi: Narosa Publishing House, 2017)
Modern Physics: Concepts and applications introduces the fundamental concepts pertaining to the basic topics of relativity, quantum mechanics and statistical mechanics along with the important sub-fields of physics, namely, atomic, nuclear and solid state physics. Besides, the technologically important topics of Superconductivity and Optoelectronics, Lasers and Nanoparticles also are introduced to a reasonable extent. The introduction of latest applications, alongwith already established ones, particularly those based on x-rays, lasers, radioactivity and condensed matter form a key feature of the book. Supported by 106 figures, 14 tables and about 100 solved problems
Includes appendix and subject index
This text-book will be useful for B.Sc. and B.E/B. Tech. Students taking up Modern Physics course, as well as for those appearing in the National Education Test (NET) being conducted by UGC-CSIR and the A.M. I.E students
Keywords: Modern physics -- Quantum theory -- Relativity - Physics -- Nuclear physics -- Atomic structure; Solid state physics